An empirical analysis of engel curve on energy for households in Sabah and Sarawak based on location and income group - Vivin Vincent Chandran; Caroline Geetha; Kwang, Jing Yii; Amran Ahmed (Western Illinois University, 2015)
The study was focused in forming an empirical model of Engel curve on energy for households in Sabah and Sarawak. Open-ended questionnaire was used as an instrument of study involving 1,002 respondents in Sabah and Sarawak. The dependent variable was budget share of energy expenditure meanwhile the independent variables were total household expenditure, age, household size, educational level, gender and regional variables. The Ordinary Least Square estimation was carried out on the cross sectional data. The coefficients were used to estimate the Engel curve expenditure elasticities. The findings revealed that total household expenditure (income) and household size were the important determinant in explaining the energy expenditure. Meanwhile the estimation of Engel curve expenditure elasticities showed that energy was a necessity good for all income groups in both urban and rural areas. Low income group was found to be more sensitive on energy expenditure to the changes in household income.